Persistence of Hepatitis B Virus Infection: A Multi-Faceted Player for Hepatocarcinogenesis - Ghosh, Suchandrima; Chakraborty, Anannya; Banerjee, Soma (Frontiers in Microbiology, 2021)
Hepatitis B virus (HBV) infection has a multi-dimensional effect on the host, which not only alters the dynamics of immune response but also persists in the hepatocytes to predispose oncogenic factors. The virus exists in multiple forms of which the nuclear-localized covalently closed circular DNA (cccDNA) is the most stable and the primary reason for viral persistence even after clearance of surface antigen and viral DNA. The second reason is the existence of pregenomic RNA (pgRNA) containing virion particles. On the other hand, the integration of the viral genome in the host chromosome also leads to persistent production of viral proteins and virion particles along with chromosomal instabilities. The interferon treatment or administration of nucleot(s)ide analogs lead to a reduction in the viral DNA load but the pregenomic RNA (pgRNA) and surface antigen clearance are a slow process and complete loss of serological HBsAg is rare. The prolonged exposure of immune cells to the viral antigens, particularly HBs antigen, in the blood circulation results in T-cell exhaustion which disrupts immune clearance of the virus and virus-infected cells. In addition, it predisposes the immune-tolerant microenvironment, which facilitates tumor progression. Thus cccDNA, pgRNA, and HBsAg along with the viral DNA could be the therapeutic targets in the early disease stages that may improve the quality of life of chronic hepatitis B patients by impeding the progression of the disease towards hepatocellular carcinoma (HCC).